Lagrangian and hamiltonian mechanics - Calkin, M G; Calkin, M G (London, World scientific, 1996)
This work takes the student from the Newtonian mechanics to the areas of more recent research. Discussion topics include invariance, Hamiltonian-Jacobi theory and action-angle variables. The final chapter introduces the dynamics of nonlinear non-dissipative systems.
Index 210-215p.
Keywords: Hamiltonian system; Legrange equation; Mathematical physics; Newton law; General Science